Students' knowledge and attitudes towards ill-effects of tobacco use in Jos metropolis of Plateau State, Nigeria - A. E. Umoh; E. C. Otoh; J. H. Jalo (Nigerian Dental Association, 2011)
Objective: Young people are vulnerable to a range of ill behaviours including tobacco use. Preventing tobacco use among youths may be an easier task than helping adults break the habit of smoking and overcome its ill effects. The objective of this study was to determine the knowledge and attitude of students towards the ill-effects of tobacco use on health. Method: This was a cross-sectional study involving secondary and tertiary school students from the Capital Teritory of Plateau State of Nigeria (Jos North, Jos South and Jos East). A twostage sampling technique was used with four secondary schools selected from each of the three Local Government Areas (LGAs). Two tertiary schools were selected from Jos South and three from Jos North proportionally to the number of schools in the two LGAs. The second stage was the selection of 661 students from the selected seventeen schools using systematic sampling procedure. A self/interviewer-administered questionnaire on smoking habits, knowledge of the different forms of tobacco, ill-effects of tobacco use, and attitude towards quitting was used for data collection. Result: The mean age was 18.09±2.11 years for secondary school students and 30.65 ±8.72 years for tertiary school students. The prevalence of tobacco use among secondary and tertiary school students were 13.6% and 22.4% respectively. More than half of the students use tobacco for social influence and cigarette was the major form of tobacco use. Majority (92.9%) of the students were generally aware of the fact that tobacco use has adverse effects on health but, the knowledge of the specific side effects was relatively low especially among current users. More than a quarter of the attempted quitters (n=68) sought advice about quitting from friends rather than health professionals. Conclusion: Knowledge of the specific hazards of tobacco use was low, especially among current users of tobacco. This study, there is an urgent need for education on tobacco and the initiation of cessation campaigns among the youths. Education on the ill-effects of unhealthy lifestyle such as tobacco use should be incorporated into secondary school curriculum. Oral health professionals, as major stakeholders, should be fully involved in these campaigns.